2000
DOI: 10.1103/physreve.61.5307
|View full text |Cite
|
Sign up to set email alerts
|

Gravity in a lattice Boltzmann model

Abstract: In this paper we consider the introduction of a body force, in the incompressible limit, into the lattice Boltzmann model. A number of methods are considered and their suitability to our objectives determined. When there is no density variation across the fluid, gravity can be introduced in the form of an altered pressure gradient. This method correctly satisfies the Navier-Stokes equation; however, if there is a non-negligible density variation present (produced by the body force or otherwise) this method bec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
164
0
3

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 295 publications
(171 citation statements)
references
References 26 publications
0
164
0
3
Order By: Relevance
“…However, general velocity and pressure boundaries are still under development for the lattice-Boltzmann method [32,33,34]. So far in most of the practical simulations a body force has been implemented [23,27,35] instead of pressure or velocity boundaries.…”
Section: Boundary Conditionsmentioning
confidence: 99%
“…However, general velocity and pressure boundaries are still under development for the lattice-Boltzmann method [32,33,34]. So far in most of the practical simulations a body force has been implemented [23,27,35] instead of pressure or velocity boundaries.…”
Section: Boundary Conditionsmentioning
confidence: 99%
“…The shift in the fluid momentum by F/2 is necessary if external forces such as gravitation are included in simulations (cf. Buick and Greated, 2000;Ginzburg et al, 2008). For the latter, one can either make use of additional force terms F q as in Buick and Greated (2000); Guo et al (2002) and set u eq = U, or equivalently work without the source term F q and use u eq = U − F/λ − instead.…”
Section: Hydrodynamic Trt-modelmentioning
confidence: 99%
“…Buick and Greated, 2000;Ginzburg et al, 2008). For the latter, one can either make use of additional force terms F q as in Buick and Greated (2000); Guo et al (2002) and set u eq = U, or equivalently work without the source term F q and use u eq = U − F/λ − instead. The latter simplifies the analysis (Ginzburg et al, 2008) and is adopted in the following.…”
Section: Hydrodynamic Trt-modelmentioning
confidence: 99%
“…In the case that forces and potentials act on the particles, there are some methods to incorporate the force term in the LBM model (Shan and Chen, 1993;Guo et al, 2002;Buick and Greated, 2000). Kupershtokh (2004) showed that the Exact Difference Method (EDM) has better accuracy compared with other methods.…”
Section: Dynamic and Thermal Lattice Boltzmann Modelmentioning
confidence: 99%